Safety, Efficacy, and Pharmacodynamics of Tremelimumab Plus Durvalumab for Patients With Unresectable Hepatocellular Carcinoma: Randomized Expansion of a Phase I/II Study. Issue 27 (20th September 2021) - Kelley, Robin Kate; Sangro, Bruno; Harris, William; Ikeda, Masafumi; Okusaka, Takuji; Kang, Yoon-Koo; Qin, Shukui; Tai, David W.-M.; Lim, Ho Yeong; Yau, Thomas; Yong, Wei-Peng; Cheng, Ann-Lii; et al.
Abstract : PURPOSE: This phase I/II study evaluated tremelimumab (anticytotoxic T-lymphocyte–associated antigen-4 monoclonal antibody) and durvalumab (antiprogrammed death ligand-1 monoclonal antibody) as monotherapies and in combination for patients with unresectable hepatocellular carcinoma (HCC), including a novel regimen featuring a single, priming dose of tremelimumab (ClinicalTrials.gov identifier: NCT02519348 ). PATIENTS AND METHODS: Patients with HCC who had progressed on, were intolerant to, or refused sorafenib were randomly assigned to receive T300 + D (tremelimumab 300 mg plus durvalumab 1, 500 mg [one dose each during the first cycle] followed by durvalumab 1, 500 mg once every 4 weeks), durvalumab monotherapy (1, 500 mg once every 4 weeks), tremelimumab monotherapy (750 mg once every 4 weeks [seven doses] and then once every 12 weeks), or T75 + D (tremelimumab 75 mg once every 4 weeks plus durvalumab 1, 500 mg once every 4 weeks [four doses] followed by durvalumab 1, 500 mg once every 4 weeks). Safety was the primary end point. Secondary end points included objective response rate (ORR) by Response Evaluation Criteria in Solid Tumors v1.1 and overall survival; exploratory end points included circulating lymphocyte profiles. RESULTS: A total of 332 patients were enrolled (T300 + D, n = 75; durvalumab, n = 104; tremelimumab, n = 69; and T75 + D, n = 84). Tolerability was acceptable across arms, with grade ≥ 3 treatment-related adverse events occurring in 37.8%, 20.8%, 43.5%, and 24.4%, respectively. Confirmed ORRs (95% CI) were 24.0% (14.9 to 35.3), 10.6% (5.4 to 18.1), 7.2% (2.4 to 16.1), and 9.5% (4.2 to 17.9), respectively. An early expansion of CD8+ lymphocytes was associated with response across arms, with highest proliferating CD8+ lymphocyte levels occurring in the T300 + D arm. The median (95% CI) overall survival was 18.7 (10.8 to 27.3), 13.6 (8.7 to 17.6), 15.1 (11.3 to 20.5), and 11.3 (8.4 to 15.0) months in the T300 + D, durvalumab, tremelimumab, and T75 + D arms, respectively. CONCLUSION: All regimens were found to be tolerable and clinically active; however, the T300 + D regimen demonstrated the most encouraging benefit-risk profile. The unique pharmacodynamic activity and association with ORR of the T300 + D regimen further support its continued evaluation in HCC.